Antecedents of Knowledge Hiding and Their Impact on Organizational Performance - Wen, Junqi; Ma, Ruijun (Frontiers in Psychology, 2021)
Research on knowledge management has been flooded in the last decade, leaving a huge gap on how, why, and what triggers knowledge hiding in inter-organizational setups. Furthermore, the fostering factors for knowledge sharing have also been remained unexplored because the employees in an organization are unwilling to share their knowledge with others for several reasons. The current study has attempted to explore those reasons that make employees hide their knowledge from other employees to excel. Those individual factors considered in this study that make employees to hide their knowledge are the lack of rewards for knowledge sharing, internal competition and psychological entitlement. Furthermore, the interesting consequent factor of knowledge hiding in this study was found significant. The moderating role of employees' social status has found a significant moderating effect on the relationship of knowledge hiding behavior and organizational performance. The population of the study is the managerial employees of financial institutions of China and the sample size taken int his study is 446 via convenient sampling technique. The independent factors in this study have found significant results on the knowledge hiding behavior, thus approving the mediating role of knowledge hiding in the organizational performance of the financial institutions of China. The software used in this study for the data analysis is smart PLS and the technique used is partial least square SEM for the measurement of the hypothesis of the study. The study's findings also have certain implications on the financial institutions for their policy making that may hinder the knowledge hiding practices and support the uninterrupted flow of knowledge among the employees.